Systemic Review of CIED extractions in the Argentinean Population - Correa Soares, Braulio; Blanco, Norberto (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Background: Implantable cardiac stimulation devices (CIEDs) are commonly used to treat cardiac rhythm disorders. However, certain circumstances may require the removal of these devices. The aim of this study is to investigate the outcomes and challenges related to CIED removal. Material and methods: A systematic review and retrospective analysis were conducted on a group of patients who underwent device removal at El Cruce Hospital. Demographic data, information about the type of device, reasons for removal, and complications were collected. Results: A total of 41 patients (average age: 50 years; 63% male) who underwent CIED removal were included in the study. The main reasons for extraction were endocarditis, generator pocket erosion, generator pocket infection, and lead failures (cables, catheter, electrode, and sensing). Complications, including technical failures, were recorded in 17% of cases. Short-term clinical outcomes were evaluated based on age, gender, device type, and reason for removal. Conclusion: In this patient community, short-term removal of cardiac devices is an effective and safe procedure with few complications. This study, based on data from a group of individuals who received treatment, while not conclusive, these findings contribute to improving the understanding of clinical practice and enhancing the quality of care received by patients in this context